Platelet Microparticles and miRNA Transfer in Cancer Progression: Many Targets, Modes of Action, and Effects Across Cancer Stages - Lazar, Sophia; Goldfinger, Lawrence E. (Frontiers in Cardiovascular Medicine, 2018)
Platelet-derived microparticles (PMPs) have long been known to increase in circulation in the presence of cancer, and have been considered to be cancer promoting by multiple mechanisms including shrouding of circulating tumor cells allowing immune evasion, inducing a procoagulant state associated with increased risk for venous thromboembolic events in cancer patients, and supporting metastatic dissemination by establishment of niches for anchorage of circulating tumor cells. These modes of PMP-enhanced progression of late stage cancer are generally based on the adhesive and procoagulant surfaces of PMPs. However, it is now clear that PMPs can also act as intercellular signaling vesicles, by fusion with target cells and transfer of a broad array of platelet-derived molecular contents including growth factors, angiogenic modulators, second messengers, lipids, and nucleic acids. It is also now well established that PMPs are major repositories of microRNAs (miRNAs). In recent years, new roles of PMPs in cancer have begun emerging, primarily reflecting their ability to transfer miRNA contents and modulate gene expression in target cells, allowing PMPs to affect cancer development at many stages. PMPs have been shown to interact with and transfer miRNAs to various blood vascular cells including endothelium, macrophages and neutrophils. As each of these contributes to cancer progression, PMP-mediated miRNA transfer can affect immune response, NETosis, tumor angiogenesis, and likely other cancer-associated processes. Recently, PMP miRNA transfer was found to suppress primary tumor growth, via PMP infiltration in solid tumors, anchorage to tumor cells and direct miRNA transfer, resulting in tumor cell gene suppression and inhibition of tumor growth. This mini-review will summarize current knowledge of PMP-miRNA interactions with cancer-associated cells and effects in cancer progression, and will indicate new research directions for understanding platelet-cancer interactions.